Metal-metal cooperation via 1,1′-bis(diphenylphosphino)ferrocene (dppf). 1. Structurally distinctive silver(I) dppf complexes of nitrato and carboxylato ligands in variable coordination modes. Crystal structures of [Ag(NO3)(dppf)]2·2CHCl3, [Ag2(HCO2)2(dppf)3]·2CH 2Cl ... - Hor, T.S.A. (2014)
Inorganic Chemistry